2013
DOI: 10.1186/1758-2946-5-36
|View full text |Cite
|
Sign up to set email alerts
|

The good, the bad and the dubious: VHELIBS, a validation helper for ligands and binding sites

Abstract: BackgroundMany Protein Data Bank (PDB) users assume that the deposited structural models are of high quality but forget that these models are derived from the interpretation of experimental data. The accuracy of atom coordinates is not homogeneous between models or throughout the same model. To avoid basing a research project on a flawed model, we present a tool for assessing the quality of ligands and binding sites in crystallographic models from the PDB.ResultsThe Validation HElper for LIgands and Binding Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…In the case of protein crystallography, the primary evidence is the electron density of the protein, ligand, and solvent molecules that form the crystal. The ability to conduct strict evidence-based validation has revealed a number of instances in which the ligands reported as bound to the protein are insufficiently supported by the primary evidence [1214]. It is important to note that there may be other lines of evidence (e.g.…”
Section: Protein–ligand Modelsmentioning
confidence: 99%
“…In the case of protein crystallography, the primary evidence is the electron density of the protein, ligand, and solvent molecules that form the crystal. The ability to conduct strict evidence-based validation has revealed a number of instances in which the ligands reported as bound to the protein are insufficiently supported by the primary evidence [1214]. It is important to note that there may be other lines of evidence (e.g.…”
Section: Protein–ligand Modelsmentioning
confidence: 99%
“…Crystal structure selection was based on the following criteria: high resolution of the crystal structure (below 3 Å) and electron density (ED) assessment. ED was evaluated using VHELIBS (32). The protein structure was obtained from the protein data bank (PDB) and Protein Preparation Wizard Maestro (Schrödinger) was used to add bond orders and hydrogen atoms to the crystal structure (33).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, CIF-like restraints dictionaries are in widespread use today because they represent the same geometry restraints function as has been found to function well with protein residues. While PDB_Redo (Cereto- Massagué et al, 2013) has shown that improvements to the quality of the model can be made, we have shown that there is a limit, when using restraint dictionaries, to how much of an improvement can be made to ligand conformation energy and geometry. As a move is made to obtain more accurate models, it is our hope that refinement target functions will more often be implemented according to the paradigm presented here (Borbulevych, Plumley et al, 2014;Smart et al, 2010Smart et al, , 2014) so as to more accurately represent the complex conformational space of small-molecule ligands.…”
Section: Discussionmentioning
confidence: 92%